Integrated Assistance Model in The Framework of Strengthening The Foundation of MSMEs - Lokita Rizky Megawati (School of Business, IPB University (SB-IPB), 2020)
The MSMEs assistance program is a model of MSMEs development that focuses on efforts to improve the institutional system (capacity building) and managerial aspects of MSMEs, which are carried out intensively and continuously, by actively involving professional MSMEs consultants. This consultant is tasked with providing consultation and coaching, specifically relating to the daily operations of MSMEs. The purpose of this paper are to 1) explain what problems are being faced as obstacles to the development of MSMEs; 2) understand the assistance requirements for MSMEs; 3) design an integrated assistance model as a solution for the development of MSMEs in Cibaduyut. This research uses a qualitative methodology. The data used consisted of primary data and secondary data. Primary data were obtained from direct field observations, in-depth interviews with UPT IKM Cibaduyut and several shoe craftsmen in Cibaduyut. Secondary data was obtained from previous research reports, journals, internet sites, and sourcebooks. The results prove that implementing the integrated assistance model are expected to improve the ability of MSMEs to analyze the results of business simulations, compile financial models so as to be able to utilize capital well, and make conclusions on the performance of companies or organizations with a high degree of accuracy and clarity. This study concludes that a asisstance program is needed to develop an independent and optimally developing MSMEs. The steps in the assistance program include planning, implementation, evaluation and development. Keywords: assistance program, Cibaduyut, integrated assistance model, MSMEs